Islamic-Based Leadership in Education: A Literature Review of Urgency, Concept, and Implementation - Wahyudienie, Mentari Bela; Hariri, Hasan; Rusdiani, Atik; Sunyono, Sunyono (Jurnal Pendidikan Progresif, 2024)
Islamic-Based Leadership in Education: A Literature Review. From an Islamic perspective, leadership issues receive considerable attention, because in Islam leadership is considered the most important instrument for the realization of an ideal society. Objectives: This article aims to examine the urgency of leadership in Islam, the concept of Islamic-based leadership in education and the implementation of Islamic-based leadership in education from various literature. Methods: This article uses a literature review method to find answers to scientific questions posed to help achieve the article's objectives by searching databases from Google Scholar and ScienceDirect with literature for the last 10 years regarding Islamic-based leadership, resulting in 27 international and national articles. Findings: The research results show that leadership is an important element in the core of Islam. Islam has provided special guidelines for selecting leaders and guiding leaders so that they can carry out their mandate to achieve the blessing of Allah Subhanahu wa Ta’ala. Islamic leadership is leadership based on the Al-Qur’an and hadith. In its implementation in education, Islamic leadership emulates the characteristics of the Prophet Shallallahu ‘alaihi wa Sallam with the main characteristics, namely: shiddiq, amanah, tabligh and fathanah. Islamic leadership in education integrates moral, spiritual, and professional growth, aligning worldly goals with worship to achieve holistic development. Conclusion: Islamic leadership is a concept rooted in the principles of the Qur'an and Sunnah, emulating the character of Prophet Shallallahu ‘alaihi wa Sallam. This leadership approach focuses not only on achieving organizational goals but also on seeking the pleasure of Allah Almighty. Islamic leadership in education includes three key dimensions: as a parent (care, commitment, responsibility), an educator (teaching with knowledge and understanding), and a leader (guiding with values and wisdom). Keywords: islamic leadership, islamic-based leadership in education, islamic perspective of leadership, prophetic leadership.DOI: http://dx.doi.org/10.23960/jpp.v14.i3.2024142